Mock patient cases are valid tools for assessing clinical pharmacy skills in undergraduate students - Rudall, Nicola; Rennie, Timothy; Singu, Bonifasius; Kibuule, Dan (Pharmacy Education, 2015)
Introduction: Namibian pharmacy undergraduate students are taught clinical knowledge and skills during clinical ward rotations. A method was sought to assess these skills using a ward scenario but under exam conditions. Assessment Method: Students were given a ‘mock’ patient case with notes and a prescription chart, plus commonly available resources, and were asked to complete a pharmaceutical care plan. Additionally students prioritised their most important three interventions identified and discussed these with a medical internist. Students were graded using a set mark scheme. Evaluation: Students demonstrated a consistent, systematic approach to clinical pharmacy review, at a competency level appropriate to undergraduates. At least three of the four key interventions were identified by 64% of students, and the average mark overall was 54%. Implementation: The assessment tool is easily adaptable to a variety of clinical pharmacy situations and levels of education and is a useful benchmark on which future assessments will be based.